Konflik antara Pete-pete (Angkot) dengan Transmaminasata (Teman Bus) di Kota Makassar: Analisis Konflik Karl Marx - Ferdiansa, Deni (Crises on Languages and Literature, 2024)
This research was triggered by the news about the presence of the Trans Maminasata Bus (Teman Bus) in Makassar City as one of the public transportation modes that can be enjoyed by the community, which gave rise to conflict. The conflict was experienced by pete-pete drivers (angkot) and the management of the Trans Maminasata Bus (Teman Bus). The author raised three news articles that would be used as samples to be analyzed using the Conflict Theory proposed by Karl Marx. In addition, the three news articles analyzed came from different sources or media. These three news articles reported the conflict between the Transmaminata Bus Management (Teman Bus) and the pete-pete drivers. In addition, this paper will also pay attention to speech as one form of lingual unit to prove and strengthen the analysis of Karl Marx's Conflict Theory. This study found that the conflict between Pete-Pete and the Trans Maminasata Bus is related to the following things: (a) the existence of a social class structure, (b) the existence of exploitation, (c) the existence of alienation or powerlessness, (d) the existence of conflicts between class interests; (e) the occurrence of lower-class struggles; and (f) the existence of social change.